The Impact of CNC Learning Module Implementation on Technical Threading Skills Using CNC Turning Machines at SMK Islam 1 Blitar - Setiawan, M Andre; Widiyanti, Widiyanti (FKIP - Universitas Riau, 2025)
Objective of the studies is to compare the impact of the application of a CNC learning module to students' technical threading skill in utilizing a CNC Turning machine at SMK Islam 1 Blitar. The studies used a quantitative method with experimental design. The sample of the studies was 144 students of two classes, experimental class that used the 2025 version of the CNC Turning learning module and control class that used the 2017 version. The instrument used to collect data was a sheet of observation of students' skill practice. The data analysis employed a linear regression method. The results indicated that the impact of the learning module on students' technical threading skill was significant, indicated by the 0.002 significance level and a regression coefficient of 3.215. The implication is that there was a corresponding increase in skill levels of students in threading with each increase in learning module use. The learning module impacted significantly on the learning of practical skills, indicated by a beta value of 0.327. A specially and practically constructed learning module has been proved to enhance students’ independent understanding and skills in line with the requirements of the industry. The CNC learning module can therefore serve as a very effective learning method to enhance competency in machining technology among students.